Confirmatory factor analysis of the Spanish version of the revised memory and behavior problems checklist. (3rd December 2014) - Nogales-González, Celia; Losada, Andrés; Romero-Moreno, Rosa
ABSTRACT: Background: Behavioral and psychological symptoms of Dementia (BPSD) are a cause of significant stress in caregivers. The revised memory and behavior problems checklist (RMBPC) (Teri et al ., 1992) is an instrument used for the assessment of BPSD. The psychometric properties of the RMBPC-Spanish version were analyzed. Method: 361 family caregivers of people with dementia were interviewed individually. The RMBPC is a 24-item questionnaire that assesses both the frequency of the BPSD and the reaction they cause in the caregiver. It has three factors: memory problems, disruptive behaviors, and depressive behaviors. Caregivers' depressive symptomatology, anxiety and burden, and the functional capacity of the person with dementia were also measured. Results: The results of a confirmatory factor analysis (CFA) show that the original three-factor model with 24 items, with error covariances, had a marginally acceptable adjustment for the frequency and reaction scales. The deletion of items with low factor loadings results in a better adjustment of the data to the model, for both the frequency and reaction scales. We found adequate internal consistency for all subscales, and significant associations between the subscales, burden, anxiety, and depression. Conclusions: The results suggest that the Spanish version of the RMBPC shows adequate adjustment for the three-factor model with 24-items, but that removing some of the items improves the adjustment. The results support the use of this instrument for the assessment of BPSD in Spanish people with dementia.